Communication Strategy of PT Citra Van Titipan Kilat in Promoting Delivery Services in Jakarta (Oratio Directa, 2022)
This study analyzes the communication strategy used by PT Citra Van Titipan Kilat (TIKI) to promote its delivery services in Jakarta, the barriers encountered, and the company's responses. It employs a qualitative descriptive approach using interviews, observation, and documentation. Data were reduced, organized, and interpreted through Anwar Arifin's four elements of communication strategy: identifying audiences, designing messages, selecting methods, and choosing media. The findings show that TIKI differentiates between existing and new customers; communicates corporate experience, awards, service excellence, discounts, invoicing, entertainment, and free pickup; repeats promotional messages; and uses Instagram, YouTube, and Facebook. The main barriers are insufficient education for new customers, unclear messages, limited promotional reach, confusion during the transition from offline to online services, and queue-related complaints. TIKI's responses include revising messages, producing more educational content, using widely adopted social media, directing customers toward online and pickup services, and responding to operational complaints. The source does not report the number or characteristics of informants or performance metrics; therefore, the findings describe the observed strategy but do not establish promotional effectiveness or sales impact.
Keywords: Communication strategy; Service promotion; TIKI; Social media; Delivery services